1998
DOI: 10.1038/32842
|View full text |Cite
|
Sign up to set email alerts
|

Negative Poisson's ratios as a common feature of cubic metals

Abstract: Poisson's ratio is, for specified directions, the ratio of a lateral contraction to the longitudinal extension during the stretching of a material. Although a negative Poisson's ratio (that is, a lateral extension in response to stretching) is not forbidden by thermodynamics, this property is generally believed to be rare in crystalline solids 1 . In contrast to this belief, 69% of the cubic elemental metals have a negative Poisson's ratio when stretched along the [110] direction. For these metals, we find tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
495
1
6

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 688 publications
(515 citation statements)
references
References 23 publications
13
495
1
6
Order By: Relevance
“…The results of many investigations [6][7] suggest that the auxetic behavior involves an interplay between the microstructure of the material and its deformation. Examples of this are provided by the discovery that metals with a cubic lattice [8] , natural layered ceramics [9] , ferroelectric polycrystalline ceramics [10] and zeolites [11] may all exhibit negative Poisson's ratio behavior. Moreover, several geometries and mechanisms have been proposed to achieve negative values for the Poisson's ratio, including foams with reentrant structures [1] , hierarchical laminates [12] , polymeric and metallic foams [13] , microporous polymers [14] , molecular networks [15] and manybody systems with isotropic pair interactions [16] .…”
mentioning
confidence: 99%
“…The results of many investigations [6][7] suggest that the auxetic behavior involves an interplay between the microstructure of the material and its deformation. Examples of this are provided by the discovery that metals with a cubic lattice [8] , natural layered ceramics [9] , ferroelectric polycrystalline ceramics [10] and zeolites [11] may all exhibit negative Poisson's ratio behavior. Moreover, several geometries and mechanisms have been proposed to achieve negative values for the Poisson's ratio, including foams with reentrant structures [1] , hierarchical laminates [12] , polymeric and metallic foams [13] , microporous polymers [14] , molecular networks [15] and manybody systems with isotropic pair interactions [16] .…”
mentioning
confidence: 99%
“…The theory of elasticity still contains some surprises, as evidenced by the realisation that the majority of cubic metals are auxetic (exhibit a Negative Poisson's Ratio, NPR) in the [110] direction (Baughman et al, 1998a), a property previously thought to be confined to few systems (Yang et al, 2004). Recent developments (Ting and Chen, 2005) have revealed the complexity of the cubic symmetry, where a change in the direction of the extreme values of Poisson's ratio from the [110] direction to near the [111] direction occurs for some combinations of the three elastic constants.…”
Section: Introductionmentioning
confidence: 99%
“…W hen stretched, materials with a negative Poisson's ratio become thicker in the direction perpendicular to the original force [1][2][3][4][5][6][7][8][9][10][11] . Materials exhibiting such counterintuitive behaviour, known as auxetics, are of great interest not only because they are rare, but also because of their numerous potential applications in various fields, such as the design of fasteners 12 , prostheses 13 , pizeocomposites 14,15 , filters 16 , earphones 17 , seat cushions 18,19 and superior dampers 20 .…”
mentioning
confidence: 99%
“…Among structural networks are molecular networks 3 , hierarchical structures 4 , composites 5 and hinged structures 22,23 . Some materials exhibit auxetic properties as they are stretched or compressed in a proper direction [6][7][8][9][24][25][26][27][28][29][30] . For example, Baughman et al 7 reported that 69% of all cubic materials exhibit a negative Poisson's ratio along the [1 10]-direction when they are subjected to stretching along the [110]-direction.…”
mentioning
confidence: 99%